Hearing Improvement after Grommet Insertion Amongst Patients of Secretory Otitis Media - Abdul Manan Khan, Aria Masoom, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Since our ability to communicate is significantly reduced without hearing, it is possible that hearing is the most significant sense in human nature. Objective: To determine the Hearing Improvement after Grommet Insertion amongst Patients of Secretory Otitis Media Methodology: This Quasi- Experimental study was conducted at the Department of ENT, Bolan Medical College / Complex Hospital, Quetta from February 2023 to July 2023 after taking approval from the research committee of the institute. Totally 40 patients were included in this study. A non-probability sequential sampling strategy was used to examine 75 ears with secretory otitis media for grommet implantation. A microscope examination was performed on both ears. The patient had tympanometry and preoperative PTA. A 20–40 dB hearing loss was deemed substantial. A grommet was positioned in the anterior inferior quadrant of the tympanic membrane during the procedure, which was carried out under general anesthesia. Results were analyzed using SPSS version 23. Results: Totally 40 patients were included in our study. The overall number of ears with secretory otitis media was 75. The male ears were 45 (60%) while female ears in our study were 30 (40%). In case of 15 (20%) ears, no hearing improvement was observed, improvement of 5-10 db was observed in 52 (69.33%) ears and improvement of 10-20 dB was observed in 8 (10.67%) ears. Conclusion: Our study concludes that hearing improves significantly in patients with secretory otitis media after grommet implantation. Keywords: Hearing; Grommet Insertion; Secretory Otitis Media